A Igreja Universal do Reino de Deus: ação social além-fronteiras - Nina Rosas (Universidade do Vale do Rio dos Sinos (UNISINOS), 2016)
This paper is an original exercise of exploring some of the social actions of the Universal Church of the Kingdom of God (UCKG) in Namibia, South Africa, Angola, Mozambique and Portugal. Taking into consideration the contingences of each region, the UCKG tries to make and link new faithful through the social action organized mainly by organizations such as Sisterhood and Woman in Action, and by the Associação Beneficente Cristã, which has been already closed in Brazil. On the one hand, the church establishes partnerships with governmental institutions in order to promote itself as a social welfare organization. On the other hand, the sisterhoods offer promises of emotional success and social reconstruction. These programs encourage women to be committed to the church routine and to discipline themselves. The resulting achievement is a vehicle of empowerment and transformation. The ethnographic material is composed of articles and stories collected from newspapers, journals, magazines, websites and blogs created by the church and that register social actions of the UCKG during 2009 and 2010.